2017
DOI: 10.1177/0004867417702748
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of the planum temporale in schizophrenia: A MRI study

Abstract: Our results showed that sexual dimorphism plays a key role on planum temporale in schizophrenia, underlining the importance of gender as a modulator of brain morphology and lateralization of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…However, in both schizophrenia and bipolar disorder, a diminished left-right hemispheric asymmetry for the 40Hz ASSRs has been shown (Teale et al 2003;Reite et al 2009;Tsuchimoto et al 2011). This is in line with an overall reduction of brain asymmetry on both the structural and functional level in neuropsychiatric disorders (Wang et al 2013;Ribolsi et al 2014;Royer et al 2015;Delvecchio et al 2017).…”
Section: Introductionsupporting
confidence: 60%
“…However, in both schizophrenia and bipolar disorder, a diminished left-right hemispheric asymmetry for the 40Hz ASSRs has been shown (Teale et al 2003;Reite et al 2009;Tsuchimoto et al 2011). This is in line with an overall reduction of brain asymmetry on both the structural and functional level in neuropsychiatric disorders (Wang et al 2013;Ribolsi et al 2014;Royer et al 2015;Delvecchio et al 2017).…”
Section: Introductionsupporting
confidence: 60%
“…Possible explanations for these contrasting results could be related to the relative small sample size or to the presence of discrepancy between males and females within the patients or the control group. In this regard, it has been reported that genderrelated differences in brain structures have been often observed in several neuropsychiatric disorders, including schizophrenia (Ruigrok et al, 2014;Delvecchio et al, 2017b). Additionally, it might be also plausible that the different methodological approaches employed by the individual studies determined these inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 39 FEP-NA patients who did not develop schizophrenia were diagnosed with: Acute transitory psychosis (n = 13), Non-organic, non-specific psychosis (n = 11), Persistent delusional psychotic syndrome (n = 7), Schizoaffective syndrome (n = 6), Acute delusional syndrome (n = 1), Acute psychosis with schizophrenic symptoms (n = 1). Patients with schizophrenia eligible for the study were selected by means of the South-Verona Psychiatric Care Register (PCR) (Tansella and Burti, 2003), a community-based mental health register, as previously reported in our publications (Delvecchio et al, 2017a(Delvecchio et al, , 2017bBrambilla et al, 2013aBrambilla et al, , 2013b. They had chronic illness.…”
Section: Participantsmentioning
confidence: 99%
“…Finally, the possibility that the healthy brain might also help us in shedding a light on brain disorders is also valid for the results observed in our group of male subjects. Indeed, GM abnormalities in the temporal gyri have been often associated with psychotic syndromes, especially with schizophrenia (Ohi et al, 2016;Delvecchio et al, 2017;Squarcina et al, 2017), which is a disorder where sexual dimorphism is well-described, with male individuals showing earlier onset, more severe course of the illness, and poorer long-term prognosis compared to matched females (Kelly et al, 2016).…”
Section: Age-related Gm Patterns In Malesmentioning
confidence: 99%